Judicial Reasoning and Sentencing Proportionality in the Teddy Minahasa Narcotics Trafficking Case - Astrid Nurindah Sari; Jonaedi Efendi; Imam Suroso (DE RECHT (Journal of Police and Law Enforcement), 2026)
This article examines judicial reasoning and sentencing proportionality in West Jakarta District Court Decision No. 96/Pid.Sus/2023/PN Jkt.Brt concerning Teddy Minahasa Putra, a senior police officer convicted of participating in narcotics trafficking. The defendant was sentenced to life imprisonment, and the sentence was subsequently upheld at the appellate and cassation levels. This study employs normative legal research using statutory, case, and conceptual approaches. Primary legal materials include the Indonesian Narcotics Law, the Police Law, the Judicial Power Law, the Criminal Procedure Code, and the relevant court decisions. The court’s reasoning is evaluated by examining the fulfilment of Article 114 paragraph (2) of Law No. 35 of 2009 in conjunction with Article 55 paragraph (1), point 1, of the Criminal Code, as well as principles of retribution, deterrence, prevention, proportionality, and substantive justice. The findings indicate that the conviction was supported by evidence of coordinated participation in the diversion and distribution of methamphetamine controlled by the police. Life imprisonment was legally available and substantively proportionate to the quantity of narcotics, the defendant’s degree of participation, the abuse of command authority, and the resulting damage to public trust. Nevertheless, the judgment should have explained more systematically how each aggravating and mitigating circumstance supported the selection of life imprisonment over other legally available sanctions. This article proposes a more structured framework for assessing judicial reasoning in serious narcotics cases involving law enforcement officers.